1998
DOI: 10.1007/s000180050241
|View full text |Cite
|
Sign up to set email alerts
|

T-cell signal transduction and the role of protein kinase C

Abstract: The T lymphocyte has a vital part to play in maintaining the host response to bacterial and viral infection and also appears to play a key pathological role in autoimmune diseases such as rheumatoid arthritis. In this review, we summarize the signalling pathways which trigger antigen-driven T-cell proliferation and examine the evidence which suggests that protein kinase C (PKC) is fundamental to this process. Finally, we discuss the therapeutic potential that PKC inhibitors may have in the treatment of autoimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 139 publications
2
15
0
Order By: Relevance
“…significant increase in the total BALF cell counts on day 9, the first day of initiation of hypersensitivity in experimental group, which further increased (3.5 fold) on day 14, similar to the findings of Sakai et al [37]. PKC is one of the key enzymes that mediate inflammatory signals [38]. It represents a structurally homologous group of 12 isoforms which are divided into three sub-groups that differ in their cofactor requirements.…”
Section: Discussionsupporting
confidence: 85%
“…significant increase in the total BALF cell counts on day 9, the first day of initiation of hypersensitivity in experimental group, which further increased (3.5 fold) on day 14, similar to the findings of Sakai et al [37]. PKC is one of the key enzymes that mediate inflammatory signals [38]. It represents a structurally homologous group of 12 isoforms which are divided into three sub-groups that differ in their cofactor requirements.…”
Section: Discussionsupporting
confidence: 85%
“…The changes were further confirmed by histopathology of the lungs, e.g. there was a significant increase in the total BALF cell counts on day 9, the first day of initiation of hypersensitivity in experimental group, which further increased (3.5fold) on day 14, similar to the findings of Sakai et al 37 PKC is one of the key enzymes that mediate inflammatory signals. 38 It represents a structurally homologous group of 12 isoforms which are divided into three sub-groups that differ in their cofactor requirements.…”
Section: +supporting
confidence: 86%
“…Their functions rely on the complete activation and cytokine production, all of which have been targeted by anti-inflammatory or immunosuppressive agents [16,17]. In this study, we used Jurkat T cells as a cellular model to evaluate the anti-inflammatory effect of CucE and found that CucE could significantly inhibit the secretion of IL-2, TNF-α, and IFN-γ in activated Jurkat T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of these cytokine genes is controlled by several critical signaling pathways including the nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways [16,17]. These signaling cascades are involved in T cell activation and cytokine expression and have been investigated as targets for immunomodulatory or immunosuppressive agents [16,17]. Thus, it is of interest to explore the effect of CucE on the responses of T cells upon mitogen stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation